Favorable outcome of ovarian germ cell malignancies treated with cisplatin or carboplatin-based chemotherapy: A hellenic cooperative oncology group study - Dimopoulos, M.A.; Papadopoulou, M.; Andreopoulou, E.; Papadimitriou, C.; N. Pavlidis; Aravantinos, G.; Aspropotamitis, A.; Anagnostopoulos, A.; Fountzilas, G.; Michalas, S.; Pectacides, D. (Gynecologic Oncology, 1998)
Purpose. To evaluate the outcome and the prognosis of patients with ovarian germ cell malignancies who were treated with platinum-based chemotherapy immediately after initial surgery. Methods. We conducted a retrospective review of patients with ovarian germ cell tumors who were referred for consideration of treatment to the Departments of Medical Oncology participating in the Hellenic Cooperative Oncology Group. Results. Over a 14-year period 53 patients were included in our study. There were 13 patients with dysgerminoma and 40 patients with nondysgerminomatous tumors. Forty percent of patients underwent complete resection of their tumors. Platinum-based chemotherapy consisted primarily of cisplatin, vinblastine, and bleomycin (PVB) in 9 patients; bleomycin, etoposide, and cisplatin (BEP) in 15 patients; and bleomycin, etoposide, and carboplatin (BEC) in 25 patients. With a median follow-up of 39 months, 5 patients developed progressive disease and died of their tumor and 1 patient died of bleomycin- induced lung toxicity with no evidence of active tumor. The 5-year overall survival was 100% for patients with dysgerminoma and 85% for patients with nondysgerminomatous tumors. Eighty percent of patients with advanced nondysgerminomatous tumors and residual disease after surgery remain disease free. Conclusion. With this study we confirm that patients with ovarian germ cell malignancies have a favorable outcome when treated with platinum-based chemotherapy.